Role and Assembly Supervisory Authority of Surakarta’s Notary in The Supervision of Notary - Agil Arya Rahmanda; Maryanto Maryanto (Jurnal Akta, 2018)
Notaries have the legal authority for the preparation of an authentic deed. To improve the quality and quantity of a Public Notary, apply to the Notary, namely Regulation No. M.02.PR08.10 Menkumham of 2004 on the Supervisory Council of Notaries. The purpose of this study was to determine the technical supervision of Notary conducted by MPD Surakarta, Role and Functions of MPD Surakarta and to determine the effectiveness of supervision MPD Surakarta in implementing the Notary supervision in the region. In this study the authors use empirical juridical approach, whereas the method of data collection using interviews and literature. The results showed that the supervision of a Notary by MPD Surakarta include: examination Notary protocols, guidance and counseling, giving approval / consent with respect to the interests of the criminal justice process to call and check Notary deed relating to the making. Notary performance Surakarta, among others: Notary of Surakarta less orderly in the making and reporting Notaries protocols, Notary unknown where the position / office address, and notaries who are rarely in the office so it was hard to see him. Barriers experienced by MPD Surakarta, among others: lack of equipment and adequate infrastructure, the limited time the members of the MPD Surakarta busy with the duties of each, a limited budget, MPD does not have the authority to impose sanctions against notaries who violate of Notary.Keywords: MPD Authority; Oversight of Notary; Notary Development.